DEVELOPING AN E-BOOK BASED INTRODUCTION TO ECONOMICS LEARNING MATERIALS USING ALDIKO CLASSIC APPLICATION FOR SOCIAL SCIENCES STUDENTS - Lailatul Rofiah; Wafiyatu Maslahah (Bajang Institute, 2021)
This research has a long-term purpose: to implement the study of introduction to economics effectively and efficiently. The learning materials developed were the non-printing type using the Aldiko Classic application so that the students do not have to spend more money to buy the printed learning material. The students just have to download the application (for free) in Playstore and install the learning materials of introduction to economics developed in such application. It was expected that the social sciences education students better understand the learning materials taught by the lecturer using the e-book and ease them to study independently. The stages in developing the e-book based learning material are as follows: 1.) analysis stage (analysis) covers the analysis of learning sources and learning material requirement, 2.) design stage (design) is to determine the learning material framework, cover learning material, layout, references, and creating assessment instrument of learning material, 3.) Development stage (Development) covers developing an e-book based learning material, experts validation and revision, 4.) implementation stage (implementation) is the trial test of learning material which has been validated, 5) Evaluation stage (Evaluation) is the stage to analyze weakness and strength of learning material which has been tested to students. The research results are 1) the development of an e-book based introduction to economics learning material has excellent feasibility because it has been conducted validation with an average score of 83% (valid). 2) the learning material of e-book based introduction to economics was declared practical to be used by the students based on the results of the response questionnaire with an average score of 77% (practical).